2018
DOI: 10.1002/jcp.27080
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E7‐induced upregulation of KDM2A promotes cervical cancer progression by regulating miR‐132–radixin pathway

Abstract: Our results suggest a function for KDM2A in cervical cancer progression and suggest its candidacy as a new prognostic biomarker and target for clinical management of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In pathological processes, such as gastric cancer and glioblastoma, LINC00460, microRNA (miRNA/miR)-29b, miR-134-5p and miR-3666 directly bind to the KDM2A promoters to regulate KDM2A expression (24,(28)(29)(30)(31). Inflammation, hypoxia or reactive oxygen species production promote KDM2A expression (26,32), and upregulation of KDM2A induced by human papilloma virus (HPV)16E7 promotes tumorigenesis and progression of cervical cancer (33). Metformin activates the AMPK signaling pathway and decreases intracellular succinic acid levels, while activation of KDM2A decreases ribosomal RNA (rRNA) transcription (27).…”
Section: Kdm2a Expression and Regulationmentioning
confidence: 99%
“…In pathological processes, such as gastric cancer and glioblastoma, LINC00460, microRNA (miRNA/miR)-29b, miR-134-5p and miR-3666 directly bind to the KDM2A promoters to regulate KDM2A expression (24,(28)(29)(30)(31). Inflammation, hypoxia or reactive oxygen species production promote KDM2A expression (26,32), and upregulation of KDM2A induced by human papilloma virus (HPV)16E7 promotes tumorigenesis and progression of cervical cancer (33). Metformin activates the AMPK signaling pathway and decreases intracellular succinic acid levels, while activation of KDM2A decreases ribosomal RNA (rRNA) transcription (27).…”
Section: Kdm2a Expression and Regulationmentioning
confidence: 99%
“…Among the five hallmarks of cancer [76] identified in this study (Figure 5), the hallmark that showed the most DEmiRNAs was sustained proliferative signaling, with 18 downregulated tsmiRs and six upregulated oncomiRs in patients with CC. Among the different miRNAs identified in this pathway, Ou et al [49] found that miR-132 can play an important role in regulating the progression of cervical cancer, contributing to the growth and progression of cervical cancer through the depression of the expression of the RDX oncogene as underlying mechanism. On the other hand, it was seen that miR-411 inhibited the progression of cervical cancer when interacting directly with STAT3; the authors also indicated that this miRNA may represent a new potential therapeutic target and prognostic marker for patients with this disease [50].…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC), Wagner et al demonstrated that KDM2A was overexpressed and could promote the proliferation and metastasis of NSCLC cells by regulating the activity of ERK1/2 pathway, which is correlated with a poor prognosis of NSCLC patients [8]. An up-regulated expression of KDM2A was also shown to play a critical role in the onset and progression of cervical cancer and promote the proliferation and invasion of cervical cancer cells [10,20]. In addition, Xu et al found that KDM2A might be an important regulator of cell proliferation and cell cycle via impacting TGF-β signaling pathway [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed KDM2A functioning as an oncogene, and its expression was elevated in lung cancer, breast cancer, and cervical cancer to promote tumorigenesis and proliferation of cancer cells [7][8][9][10]. On the contrary, Frescas et al found that KDM2A expression was often decreased in prostate cancer compared with normal prostate tissue [11].…”
Section: Introductionmentioning
confidence: 99%